Development of the in-situ Calibration System using LEDs and Light Guide Plates for the SuperFGD. Issue 1 (1st November 2022) - Arihara, T; Boikov, A; Davydov, Yu I; Drapier, O; Kakuno, H; Matsubara, T; Tereshchenko, S; Tereshchenko, V
Abstract : T2K is a long-baseline neutrino experiment that aims to investigate the CP violation in the neutrino sector. An upgrade of the ND280, which is one of the T2K near detectors, is in progress. The active target detector of the upgraded ND280 is a segmented highly granular plastic scintillation detector (SuperFGD) consisting of about two million scintillator cubes. About sixty thousand silicon photo-multipliers (SiPMs) coupled with wavelength shifting fibers are used for light readout. The fibers go through the scintillator cubes along the orthogonal three directions. We developed a novel system based on LEDs and notched light guide plates for in-situ calibration of the SuperFGD. The developed system can distribute LED light to SiPMs simultaneously with high uniformity and can be used for gain calibration and stability monitor of the signal readout. In addition, it can fit in the confined space of the SuperFGD due to its thin structure. In this paper, we report the design and the performance of the calibration system.